2009
DOI: 10.1016/j.jsams.2007.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The lifestyle of our kids (LOOK) project: Outline of methods

Abstract: This methods paper outlines the overall design of a community-based multidisciplinary longitudinal study with the intent to stimulate interest and communication from scientists and practitioners studying the role of physical activity in preventive medicine. In adults, lack of regular exercise is a major risk factor in the development of chronic degenerative diseases and is a major contributor to obesity, and now we have evidence that many of our children are not sufficiently active to prevent early symptoms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 16 publications
0
44
0
2
Order By: Relevance
“…Recruitment methods for this community-based longitudinal study have been described previously. 12 In brief, the Lifestyle of Our Kids Study is a prospective cohort study designed to investigate the effect of physical activity on health and development. Participating children were recruited from local primary (elementary) schools in which average family income was very close to that of the Australian national average.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recruitment methods for this community-based longitudinal study have been described previously. 12 In brief, the Lifestyle of Our Kids Study is a prospective cohort study designed to investigate the effect of physical activity on health and development. Participating children were recruited from local primary (elementary) schools in which average family income was very close to that of the Australian national average.…”
Section: Methodsmentioning
confidence: 99%
“…12 Supine brachial BP and heart rate were determined using an automated oscillometric Omron 7051T. The average of 2 measurements made at 1-minute intervals was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…However, this year the RWG decided to raise the bar for this indicator, and the primary metric used to assign the grade was changed to "the percentage of school students for which active transport is their usual mode of transport to and from school at least part of the way (defined as at least 5/10 trips or on at least 2.5/5 days)." New state-based data were considered in addition to the data considered in the 2015 Progress Report Card (see Table 1), which collectively showed that approximately 41% to 43% of secondary students 5,25 and 23% to 38% of primary school students 18,19,22,25,26 use active transport as their 'usual mode' of transport to/from school at least part of the way. Even though new data were considered, the grade decline this year was a result of the RWG deciding to 'raise the bar' rather than actual participation rates declining.…”
Section: Active Transportation: C-mentioning
confidence: 99%
“…In addition to the statebased data considered in 2014, 29 new state-based data were available in 2016. 22,37 Collectively, these data, which represented more than 5800 9-to 16-year-olds from multiple states and territories who were directly measured using the 20 m shuttle run (20mSRT), were believed by the RWG to be sufficient to confidently inform a grade. Relative to sex-specific and age-specific international normative 20mSRT values generated on 1,142,026 children and young people from 50 countries, 38 Australian children and young people are of below average aerobic fitness (mean ± 95% confidence interval: 43 ± 5 percentile).…”
Section: Government-strategies Policies Investments: Dmentioning
confidence: 99%
“…In 2005 a cohort of healthy 8-year-old children was enrolled from Canberra schools, assigned to intervention and control groups, and followed for 4 years. The details of this study have been published elsewhere (11 ).…”
Section: Study Participantsmentioning
confidence: 99%